Effect of Work Discipline and Compensation on Employee Performance Majalengka Company People's Credit Bank, West Jawa - Pernanda, Rianto; Hartono, Edy; Wibowo, Sandi Nasrudin (Journal Socio Humanities Review, 2021)
This study aims to determine the effect of Work Discipline and Compensation on Employee Performance at PT. Majalengka Rural Bank, West Java. The research method used is a quantitative research method. The population in this study were employees of PT. Majalengka Rural Bank, West Java. The technique used in sampling is saturated sample, where the total population is used as a sample of 57 respondents. The method of collecting data is using a questionnaire, while the method in this study uses multiple linear regression analysis.The results of this study indicate that Work Discipline has a significant effect on Employee Performance as seen from tcount > ttable that is 3.863 > 2.00404, Compensation has a significant effect on Employee Performance seen from tcount > ttable that is 4.866 > 2.00404 and simultaneously Work Discipline and Compensation have a positive and significant effect on Performance Employees are shown from Fcount > Ftable which is 14,804 > 3,17. From the partial results of Work Discipline has a sig value of 0.000 and Compensation has a sig value of 0.000, and the simultaneous results have a sig <0.05 or 0.000 <0.05.